On a Novel Fourth-Order Algorithm for Solving Systems of Nonlinear Equations - Diyashvir K. R. Babajee; Alicia Cordero; Fazlollah Soleymani; Juan R. Torregrosa (Journal of Applied Mathematics)
This paper focuses on solving systems of nonlinear equations numerically. We propose an efficient iterative scheme including two steps and fourth order of convergence. The proposed method does not require the evaluation of second or higher order Frechet derivatives per iteration to proceed and reach fourth order of convergence. Finally, numerical results illustrate the efficiency of the method.